MUSICAL COMMUNICATION AND EPIDEMIC: THE ROLE OF MUSIC IN THE COVID-19 EPIDEMIC - Tanyıldızı, Nural İmik (İnönü Üniversitesi, 2020)
Since ancient times, there has been a lot of information that music has deeply affected the human psyche. It is seen that music is the food of the human psyche and is used even in the treatment process of some diseases. It also includes a communication process in music. The messages given by musical communication have different effects on the target audience. COVID-19 disease, which started at the end of 2019 and spread all over the world in a short time, has affected people in many areas. One of the areas most affected by COVID-19 is human psychology. In this study, the effects of musical communication on the human psyche during the COVID-19 process were examined. Qualitative research method was used in this study. Semi-structured interview technique was used in the research. For this purpose, pre-prepared interview questions were asked to 30 people through online interviews. The obtained data were recorded by the researcher. The data were analyzed by the qualitative research method. It has been trying to determine how music affects the human psyche during the pandemic process.

Eski çağlardan beri müziğin insan ruhunu derinden etkilediğine yönelik birçok bilgiye ulaşılmaktadır. Müziğin insan ruhunun gıdası olduğu ve bazı hastalıkların tedavi sürecinde bile kullanıldığı görülmektedir. Müzik içerisinde aynı zamanda bir iletişim sürecini barındırmaktadır. Müziksel iletişim ile verilen mesajlar hedef kitleler üzerinde farklı etkiler yapmaktadır. 2019 yılının sonunda başlayan ve kısa surede tüm dünyaya yayılan COVID-19 hastalığı insanları birçok alanda etkilemiştir. COVID-19’un en çok etkilediği alanlardan biri de insan psikolojisidir. Bu çalışmada COVID-19 sürecinde müziksel iletişimin insan ruhuna etkileri incelenmiştir. Bu çalışmada nitel araştırma yöntemi kullanılmıştır. Araştırmada yarı yapılandırılmış görüşme tekniği uygulanmıştır. Bu amaçla 30 kişiye önceden hazırlanmış mülakat soruları çevrimiçi görüşme ile sorulmuştur. Elde edilen veriler araştırmacı tarafından kayıt altına alınmıştır. Veriler nitel araştırma yöntemi ile analiz edilmiştir. Pandemi sürecinde müziğin insan ruhunu nasıl etkilediği belirlenmeye çalışılmıştır.
SALGIN VE MÜZİKSEL İLETİŞİM: COVİD-19 SALGININDA MÜZİĞİN ROLÜ